Prognosis and the Effect of De-Escalation of Antiplatelet Therapy After Nuisance Bleeding in Patients With Myocardial Infarction. (16th November 2022) - Choo, Eun Ho; Choi, Ik Jun; Lim, Sungmin; Moon, Donggyu; Kim, Chan Joon; Park, Mahn-Won; Kim, Min Chul; Hwang, Byung-Hee; Lee, Kwan Yong; Seok Choi, Yun; Kim, Hee-Yeol; Yoo, Ki-Dong; et al.
Abstract : Background: Data regarding prognosis and management after nuisance bleeding (NB) is limited. The purpose was to examine the prognostic significance of NB in patients receiving potent dual antiplatelet treatment (DAPT) after acute myocardial infarction and the impact of de-escalation of DAPT on clinical outcomes thereafter. Methods: From the TALOS-AMI trial (Ticagrelor Versus Clopidogrel in Stabilized Patients With Acute Myocardial Infarction)‚ 2583 patients were used to investigate the clinical impact of NB (defined as Bleeding Academic Research Consortium [BARC] 1 bleeding) during 1-month treatment with ticagrelor-based DAPT after acute myocardial infarction. We assessed the associations between NB within 1 month and BARC 2, 3, or 5 bleeding and major adverse cardiovascular event (a composite of cardiovascular death, myocardial infarction, stroke) from 1 to 12 months. We also evaluated the effect of de-escalation to clopidogrel in patients with or without NB. Results: NB occurred in 416 patients (16.7%) after 1 month of ticagrelor-based DAPT. At 1 year, NB was not associated with increase in BARC 2, 3, or 5 bleeding (hazard ratio [HR]‚ 1.29 [95% CI‚ 0.7–2.14]) and major adverse cardiovascular event (HR‚ 1.72 [95% CI‚ 0.87–3.39]). However, patients with NB had an increased risk of BARC 2, 3, or 5 bleeding at 6 months (HR, 1.94 [95% CI, 1.08–3.48]; P =0.026), which diminished over the next 6 months. De-escalation from ticagrelor to clopidogrel reduced the incidence of BARC 2, 3, or 5 bleeding compared with ticagrelor plus aspirin in NB (HR‚ 0.31 [95% CI‚ 0.10–0.92]) and non-NB patients (HR‚ 0.58 [95% CI‚ 0.37–0.90]) without heterogeneity ( P interaction=0.291). There was no increase in major adverse cardiovascular event after DAPT de-escalation, irrespective of NB. Conclusions: NB was frequent in patients with acute myocardial infarction on 1-month ticagrelor-based DAPT and was associated with an early increase of bleeding. DAPT de-escalation after NB may reduce bleeding without increasing ischemic events. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02018055.